Can an intervention based on a serious videogame prior to cognitive behavioral therapy be helpful in bulimia nervosa? A clinical case study - Giner-Bartolomé, Cristina; Fagundo, Ana B.; Sánchez, Isabel; Jiménez-Murcia, Susana; Santamaría, Juan J.; Ladouceur, Robert; Menchón, José M.; Fernández-Aranda, Fernando (Frontiers in Psychology, 2015)
Background: Several studies have highlighted the implications of impulsivity and novelty seeking for both the maintenance and the process of recovery from bulimia nervosa. Cognitive behavioral therapy (CBT) is the treatment of choice for bulimia nervosa, but for some cases, this treatment alone might not be sufficient for reducing the high levels of impulsivity. The paper presents a case report of a patient with bulimia nervosa, examining the effectiveness of using a videogame (Playmancer) as an additional intervention designed to address impulsivity. Design: Psychometric and neuropsychological measures were collected at baseline. After this assessment, Playmancer was applied prior to CBT, following an “A-B-A-C-A” single case experimental design. Impulsivity levels were assessed with the Conners’ Continuous Performance Test II (CPT-II). After the Playmancer treatment, the patient started CBT, and the levels of impulsivity were recorded again. Finally, psychometric and neuropsychological measures were collected after treatment. Weekly frequency of binges and vomiting were also recorded during the entire procedure. Results: After the videogame intervention, psychometric measures such as anxiety levels, impulsivity and novelty seeking decreased. Regarding the neuropsychological measures, impulsivity levels (measured with the CPT-II) progressively decreased throughout the intervention, and an improvement in decision making capacities was observed. Furthermore, the frequency of binges also decreased during and after the videogame intervention. Discussion: This case report suggests that using the Playmancer videogame to reduce impulsivity prior to CBT may enhance the final results of the treatment for bulimia nervosa.